2020
DOI: 10.1016/j.compedu.2019.103732
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Acceptance of Mobile Library Applications with an Extended Technology Acceptance Model (TAM)

Abstract: Mobile applications are getting a great deal of interest among researchers due to their proliferation and pervasiveness, especially in the context of digital libraries of educational institutes. However, their low acceptance and usage are observed, hence, in-depth investigations are required in order to understand the factors behind low acceptance and intention to use mobile library application (MLA). Therefore, the aim of this work is to empirically explore the acceptance of MLA with a proposed model that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
214
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(245 citation statements)
references
References 38 publications
19
214
2
10
Order By: Relevance
“…For the first three hypotheses, the focus was on the factors of PEU and PU. The hypotheses seem to be consistent with previous studies, that is, the fact that usefulness of Google Meet is governed by its of ease of use seems to be agreed upon by much prior research where colleges and universities were encouraged to focus on the factors of usefulness and ease of use (Martín-García et al, 2019;Rafique et al, 2020). For the fourth hypothesis, where SN factor was investigated, the results have shown that peer's opinions have an effective role in creating an influential educational environment.…”
Section: Discussionsupporting
confidence: 83%
“…For the first three hypotheses, the focus was on the factors of PEU and PU. The hypotheses seem to be consistent with previous studies, that is, the fact that usefulness of Google Meet is governed by its of ease of use seems to be agreed upon by much prior research where colleges and universities were encouraged to focus on the factors of usefulness and ease of use (Martín-García et al, 2019;Rafique et al, 2020). For the fourth hypothesis, where SN factor was investigated, the results have shown that peer's opinions have an effective role in creating an influential educational environment.…”
Section: Discussionsupporting
confidence: 83%
“…Several previous studies on the TAM have revealed the consistent results in which perceived usefulness has strongly influenced the intention to use technology. TAM postulates that perception of usefulness is affected by perceived ease of usage since the easier it is to use a system; it can be the more useful [26]. Understanding the determinants of perceived ease of usage would enable intervention in the business, thereby making it possible to augment the adoption and usage of innovation.…”
Section: A Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Vehicle speed and position can be visualized using ONE Simulator [28]. Routing decisions are conducted using estimation time [29]. The source node generates a message bundle and searches for a node to carry that message bundle.…”
Section: Methodsmentioning
confidence: 99%